Identification of Premature Infants at High Risk of Late Respiratory Diseases: A Retrospective Cohort Study - Sun, Ling; Bao, Yingying; Zhang, Hong; Zhu, Jiajun (Frontiers in Pediatrics, 2022)
Aim: To identify infants with very low birth weight at risk of late respiratory diseases after discharge. Methods: This retrospective longitudinal study included 388 preterm infants with gestational age of <32 weeks and birth weight of <1,500 g and evaluated perinatal information, assessments performed while in the neonatal intensive care unit, and longitudinal follow-up via questionnaire until the corrected gestational age of 18-24 months. Results: The mean birth weight and gestational age were 1,191.2 ± 191.8 g and 29.1 ± 1.4 weeks, respectively. Sixty-four (16.5%) infants developed late respiratory diseases after discharge to the corrected gestational age of 18-24 months. Univariate analyses showed that gestational age, birth weight, respiratory support, oxygen use, bronchopulmonary dysplasia dignosed at 36 weeks’ postmenstrual age and length of hospital stay were associated with late respiratory diseases. After adjusting for covariates, respiratory support was significantly associated with serious respiratory morbidities to 18-24 months corrected gestational age. With each day of respiratory support, the odds of late respiratory diseases increased by 1.033-fold. Conclusions: Respiratory support was associated with increased odds of developing late respiratory diseases during early childhood, which may be an early predictor to late respiratory morbidities. Thus, it is imperative to identify a safe and effective strategy to prevent chronic dependency on respiratory support.